Development and Test Research of Shift Performance Test System of Manual Transmission - Yu Xiaoxia; Zhang Zhigang; Hou Yabin; Ou Xin (Jixie chuandong)
The influence factors of static shift performance and dynamic shift performance of manual transmission are analyzed. Because of requirements of gear shift performance test,the mechanical system and software system of transmission shift performance test rig are designed. Based on the developed test bench,static shift performance and dynamic shift performance test of a transmission are carried out. The static shift test shows that the designed test system can accurately measure performance parameters of transmission shift mechanism,such as track selection,gear clearance and select stiffness. The dynamic shift performance test shows that the designed test rig can measure performance parameters of shift force,lever travel and transmission input speed,and it can detected whether there are double bump in the shift process.